QUALITATIVE AND QUANTITATIVE CHARACTERS OF THREE COMMON CARP (Cyprinus carpio L.) STRAINS IN INDONESIA - Harton Arfah; Dinartri Soelistyowati (Institut Pertanian Bogor, 2004)
The second generation of gynogenetic diploid common carp of majalaya, sinyonya and mirror strains have been produced in 1992. Some of them were sex-reversed by oral administration of 17 α-methyltestoteronne. The females and sex-reversed males were matured on early 1994 and mated to produce progenies ofpure strains. This research aimed to measure certain quantitative characters since the early stage of developmentto the market size. Three different conditions of rearing (i.e. rice field, ponds and concrete tanks) were applied during the nursery phase, while the earthen pond and running water system with intensive feeding were used for the grow-out stage. The results showed that average fecundity of sinyonya carp was higherthan mirror and majalaya strains, but its performances of the early development (i.e. fertilization rate, hatching rate and survival rate at 14 days old) was lowest. At the nursery phase, the survival and growth rates of majalaya carp was relatively better than the other two strains, but the mirror carp had highest feed efficiency and lowest protein retention. During culture period, the growth rates of these three common carp strains were relatively similar (1%), but sinyonya carp, among strains had the highest percentage of fillet (38.5%) with the lowest total number of muscular bones (69), the highest level of protein content (77.5%) and the lowest level of lipid content (16.6%) among the three strains. Keywords: Cyprinus carpio L, gynogenesis, growth rate, product quality.